Menggagas Pendidikan Islami: Meluruskan Paradigma Pendidikan di Indonesia - Tatang Hidayat; Toto Suryana (Program Pascasarjana Universitas Ibrahimy, 2018)
The aim of this present study is to initiate Islamic education in order to rectify the educational paradigm in Indonesia. With respect to the research methodology, this study employed a qualitative approach and literature study method. In its implementation, the collected data was then analyzed using a descriptive analysis method. Based on the results of the discussion, in order to rectify the educational paradigm in Indonesia, it should initially change the secularism paradigm that has been fossilized in the world of education into the paradigm of Islam, al-Qur`an, and Tauhid. As a consequence, this paradigm will have implications for the establishment of the conceptualized education system that inevitably also affects the to-be-achieved educational objectives. In order to realize a good education system, there should be integration between the elements of education practitioners which consist of family, mosques/schools/campuses, and society. As a result, those aforementioned objectives will be successfully achieved in the moment when Islamic rules are fully implemented in all aspects of life. Therefore, it is necessary to continuously educate the public regarding the importance of implementing Islamic rules in all aspects of life, including in the aspect of education.